The Economic Effects of Special Purpose Entities on Corporate Tax Avoidance - Demeré, Paul; Donohoe, Michael P.; Lisowsky, Petro (Contemporary Accounting Research, 2020)
ABSTRACT This study provides the first large‐sample evidence on the economic tax effects of special purpose entities (SPEs). These increasingly common organizational structures facilitate corporate tax savings by enabling sponsor firms to increase tax‐advantaged activities and/or enhance their tax efficiency (i.e., relative tax savings of a given activity). Using path analysis, we find that SPEs facilitate greater tax avoidance such that an economically large amount of cash tax savings from research and development (R&D), depreciable assets, net operating loss carryforwards, intangible assets, foreign operations, and tax havens occur in conjunction with SPE use. We estimate that SPEs help generate over $330 billion of incremental cash tax savings, or roughly 6 percent of total U.S. federal corporate income tax collections during the sample period. Interaction analyses reveal that SPEs enhance the tax efficiency of intangibles and R&D by 61.5 percent to 87.5 percent. Overall, these findings provide economic insight into complex organizational structures supporting corporate tax avoidance.